Die Hilfe für kranke und alte Menschen in der postmodernen Gesellschaft nach Papst Franziskus - Celary, Ireneusz (Poznańskie Studia Teologiczne, 2016)
The situation of the elderly and ill in the contemporary postmodern society constitutes a serious challenge for contemporary societies as well as for pastoral work of the Church. Reflections of Pope Francis describing the fate of the elderly and ill in the contemporary reality are to be found in the above article. The issue has been discussed in the following subsections: “Competences of the postmodern society towards the elderly and ill” (chapter I); “The significance of the Christian community for the life of the elderly and ill” (chapter II); “The objectives of the pastoral conversation” (chapter III).